Structural insights into the mycobacteria transcription initiation complex from analysis of X-ray crystal structures - Elizabeth A. Hubin (Nature Portfolio, 2017)
Understanding of the mycobacterial transcription system is useful to the development of therapeutics against tuberculosis infection. Here the authors present the crystal structure of a completeM. smegmatisRNA polymerase open promoter complex that reveals unique features of the mycobacterial polymerase.